2002
DOI: 10.1097/00005768-200212000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy alters recruitment of the vasti in patellofemoral pain syndrome

Abstract: This study demonstrates that a "McConnell"-based physical therapy treatment regime for PFPS alters the motor control of VMO relative to VL in a functional task and this is associated with a positive clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
152
0
31

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(193 citation statements)
references
References 23 publications
10
152
0
31
Order By: Relevance
“…7,[12][13][14][15]22,39,40,42 However, few of these studies evaluated the efficacy of isolated quadriceps strengthening. Many published rehabilitation protocols target functional exercises in a weight-bearing position, which requires a contribution of both hip and quadriceps musculature.…”
Section: T T Conclusionmentioning
confidence: 99%
“…7,[12][13][14][15]22,39,40,42 However, few of these studies evaluated the efficacy of isolated quadriceps strengthening. Many published rehabilitation protocols target functional exercises in a weight-bearing position, which requires a contribution of both hip and quadriceps musculature.…”
Section: T T Conclusionmentioning
confidence: 99%
“…Some studies have analyzed the beginning of voluntary electrical activity of the median and lateral stabilizing muscles of the patella in clinically healthy and individuals with PPS, and have demonstrated synchronism of these muscles under different functional conditions 13 . However, other authors have not observed this synchronism when comparing the beginning of the electrical activity of the (VMO) and vastus lateralis (VL) muscles between normal individuals and those with PPS 2,7 . The beginning of this activity has been used to evaluate the neuromuscular response time of the patellar stabilizing muscles and also how the effect of carrying out treatment protocols on individuals with PPS influences this parameter 12,14,15 .…”
Section: Introductionmentioning
confidence: 95%
“…The patellofemoral pain syndrome (PPS) frequently affects female athletes, the female sedentary population, and young women are most affected [1][2][3] . This syndrome is present in approximately 25% of orthopedic diagnoses 4 and is defined as a pain at the front of the knee and/or rear of the patella [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations